Risk factors associated with depression among chronic heart failure patients in Pakistan; A Systematic Review - Saima Dastgeer , Muhammad Saleem (Journal of Rawalpindi Medical College, 2021)
Abstract Objective: To systematically review the number of studies carried out to find the risk factors associated with depression among chronic heart failure patients in Pakistan. Methods: A systematic and methodological search strategy was established by using key words i.e., depression, heart failure, Pakistan, risk factors on databases such as Science Direct, PubMed, Research Gate, PakMedinet, JSTER and Emerald Insight. Data screening for a period of ten years i.e., 2010 to 2020 identified 771 studies while only 59 met the inclusion criteria. Only 6 out of 59 studies were declared eligible for meticulous review. Results: Out of total search result of 771 articles, 59 (8%) full text Pakistani articles were found. Altogether 06(10%) studies met the inclusion criteria and selected for systematic review. Conclusion: Depression among chronic heart failure patients in Pakistan is predominately linked with lack of social support, lower socioeconomic status, sedentary life style, sleep disturbance and old age. Furthermore, severity and duration of the disease, prior history of acute myocardial infarction, repeated hospitalization and co-morbidities were also reported as disease linked depression risk factors. Keywords: Depression, Chronic heart failure, risk factors, Pakistan